Pengaruh Media Tanam dan Frekuensi Penyiraman Terhadap Pertumbuhan dan Hasil Selada (Lactuca sativa L.) Sistem Vertikultur - Muhammad Hatta; Erida Nurahmi; Wahyuni Sari (Fakultas Pertanian, Universitas Syiah Kuala, 2009)
Effect of Growing Media and Sprinkling Frequency on Growth and Yield of Lettuce (Lactuca sativa L.) in Verticulture SystemAbstract. This study aims to determine the influence of growing media and watering frequency on growth and yield of lettuce using verticulture system and the interaction between the two factors. The design used was randomized block design (RBD) with factorial pattern. 4x3 and 3 replications, so there were 36 experimental units. There are two factors studied, namely factor planting medium (M) consist of four level, and watering frequency factor (P) consisting of three levels. The result showed that the effect of growing media and watering frequency on lettuce plant significantly to the growth and yield of lettuce plant, including plant height, length, width, and number of strands of lettuce of the age of 10, 20, 30 days after planting (DAP) and wet weight age 30 DAP. The best planting medium found in the soil planting medium. While the best watering frequency found 1 day 2 times. There was no significant interaction between the growing media and watering frequency on all growth variables and lettuce plants were observed.